p–n-Sensitized Heterostructure Co3O4/Fullerene with Highly Efficient Photoelectrochemical Performance for Ultrasensitive DNA Detection - Wang, Hai-Hua; Li, Meng-Jie; Wang, Hai-Jun; Chai, Ya-Qin; Yuan, Ruo (ACS applied materials & interfaces, 2019)
Significantly sensitized architectures meeting the requirements of high photoelectric conversion efficiency and promising photocurrent intensity are extremely desirable, but challenges in sensitizer development and efficiency in photoelectrochemical (PEC) fields remain. In this paper, the p-type metal oxide semiconductor Co3O4 was attached as an effective photosensitizer to n-type fullerene C60 in view of appropriately matched energy band levels to form the highlighted p–n-sensitized heterostructure Co3O4/fullerene, with facilitated charge separation and accelerated carrier mobility. Compared with traditional p–n heterostructure, the p–n-sensitized heterostructure Co3O4/fullerene illustrated a wider range for light absorption with further enhanced light-harvesting capability, thereby leading to more exceptional PEC performance containing remarkably promoted photoelectric conversion efficiency and improved photocurrent intensity. Impressively, the photocurrent intensity obtained by Co3O4/fullerene was about sixfold higher than that of fullerene alone, and this achievement was quite favored compared to the reported works for fullerene sensitization, which could be responsible for the advancement of detection sensitivity for the subsequently constructed biosensor. Unambiguously, given the p–n-sensitized heterostructure Co3O4/fullerene of high PEC activity, the well-fabricated three-dimensional DNA walker applied as a target-cascade signal amplification strategy, and the Au layer employed as the specific linker between the photoactive material and the signal amplification product, a smart PEC biosensor was successfully enabled for ultrasensitive investigation of the model DNA (a fragment of the p53 gene), showing a wide linear range of 60 to 1 × 105 aM and a detection limit of 20 aM. This proposed PEC biosensor provided acceptable insights into the clinic analysis, disease therapies, and other relevant subjects.